The empirical results of conditional analysis of principals' reasons in bullying teachers - Setiawan, Roy; Kumar, V. Ramesh; Chakravarthi, M. Kalyan; Villalba-Condori, Klinge Orlando; Vera-Vasquez, Cesar Gonzalo; Subramaniam, Tamil Selvan; Koti, Kartikey; Rajest, S. Suman; Rajan, Regin (2021)
Starting from the bullying of teachers by principals, this paper elaborates (a) how incompetency of management favours its emergence, (b) how teachers can see it, and (c) whether this problem affects the performance of teachers or not. The empirical results show that motivation, a positive workplace, and not being bullied or agitated by principals increase teachers' performance. The findings show that the teachers consider management's incompetency the major factor to be blamed. Collaboration between teachers can have a role in limiting this abuse. Because management is the key obligation for clearing the ethos and function of the company and clarifying the translation of words into the organization, there is some laggard of management in the way the control extracted from the structured authority is confused. Success strain!! In the light of the short- and long-term priorities and plans,